The Irish Parliamentary Diary (1776–89) of Sir Henry Cavendish. (October 2016) - Thomas, P.D.G.
Abstract : This article clarifies the history of the 'parliamentary diary' compiled by Sir Henry Cavendish while a member of the Irish parliament between 1776 and 1789, correcting misapprehensions in previous accounts, in particular the assertion by A.P.W. Malcomson and D.J. Jackson that Cavendish paid less attention to recording debates in the 1780s.